2015
DOI: 10.7326/m15-1150
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Peripheral Thermometers for Estimating Temperature

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(161 citation statements)
references
References 122 publications
10
132
1
7
Order By: Relevance
“…The acceptable limit of difference between two temperature monitoring devices is generally reported as ±0.5°C in both human and animal studies (Greer et al, 2007;Sousa et al, 2011;Lamb and McBrearty, 2013;Niven et al, 2015). Using the raw data collected in this study, 31.6% of TMT readings fell outside the accepted 0.5°C difference, similar to the findings reported by Lamb and McBrearty (2013).…”
Section: Discussionsupporting
confidence: 78%
“…The acceptable limit of difference between two temperature monitoring devices is generally reported as ±0.5°C in both human and animal studies (Greer et al, 2007;Sousa et al, 2011;Lamb and McBrearty, 2013;Niven et al, 2015). Using the raw data collected in this study, 31.6% of TMT readings fell outside the accepted 0.5°C difference, similar to the findings reported by Lamb and McBrearty (2013).…”
Section: Discussionsupporting
confidence: 78%
“…Statistical analyses to detect reporting bias were not conducted due to lack of validated methods 8. Although some meta-analyses of method comparison studies have used tests for detecting funnel plot asymmetry,9 simulations have revealed that such tests will result in publication bias being incorrectly identified too often 10…”
Section: Methodsmentioning
confidence: 99%
“…Although these thermometers provide the most accurate assessment of core body temperature, they are not commonly employed as the primary method of temperature measurement in critically ill patients. Rather, temperature is commonly measured using thermometers that measure temperature from a peripheral site (e.g., tympanic membrane, temporal artery, axilla, mouth) and use proprietary algorithms to convert the measured temperature into a core temperature [22, 23]. Unfortunately, peripheral thermometers are among the least accurate, especially in patients with fever or hypothermia.…”
Section: Body Temperature Measurement and Definitionsmentioning
confidence: 99%